2018
DOI: 10.3892/ijo.2018.4427
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic kinase PBK/TOPK as a therapeutic target for adult T‑cell leukemia/lymphoma

Abstract: Adult T‑cell leukemia/lymphoma (ATLL) is a disorder involving human T-cell leukemia virus type 1 (HTLV‑1)-infected T‑cells characterized by increased clonal neoplastic proliferation. PDZ-binding kinase (PBK) [also known as T‑lymphokine-activated killer cell-originated protein kinase (TOPK)] is a serine/threonine kinase expressed in proliferative cells and is phosphorylated during mitosis. In this study, the expression and phosphorylation of PBK/TOPK were examined by western blot analysis and RT‑PCR. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
1
24
1
Order By: Relevance
“…Thus, PBK activates downstream signaling cascades via its phosphorylated substrates and plays an important role in many kinds of cellular processes, including growth, development, apoptosis, and inflammation 36 . Previous studies including our group have highlighted that PBK was required for malignant phenotypes and was associated with poor prognosis of human common cancers, including NPC, oral cancer, breast cancer, colorectal cancer, leukemia and lymphoma, ovarian cancer, lung cancer, and glioma 34,[36][37][38][39][40] . Due to the broad expression of PBK across multiple tumor types, specific inhibitors have been developed to target PBK, including HI-TOPK-032 41 , OTS514/OTS964 42 , and ADA-07 43 , and show high therapeutic potency in the preclinical study.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PBK activates downstream signaling cascades via its phosphorylated substrates and plays an important role in many kinds of cellular processes, including growth, development, apoptosis, and inflammation 36 . Previous studies including our group have highlighted that PBK was required for malignant phenotypes and was associated with poor prognosis of human common cancers, including NPC, oral cancer, breast cancer, colorectal cancer, leukemia and lymphoma, ovarian cancer, lung cancer, and glioma 34,[36][37][38][39][40] . Due to the broad expression of PBK across multiple tumor types, specific inhibitors have been developed to target PBK, including HI-TOPK-032 41 , OTS514/OTS964 42 , and ADA-07 43 , and show high therapeutic potency in the preclinical study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PBK plays a major role in mitotic phosphorylation, regulation of DNA damage repair, tumorigenesis, and therapeutic resistance through various protein phosphorylation reactions [9,10]. Increasing evidence has shown that excessive activation of PBK contributes to tumor proliferation, invasion, as well as treatment failure in a variety of tumor types [[11], [12], [13]]. Recent studies demonstrated that overexpression of PBK was correlated with poor prognosis of hepatocellular carcinoma and promoted migration and invasion of tumor cells through ETV4-uPAR signaling pathway [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to find TOPK inhibitors with low toxicity to overcome the side-effect of current TOPK inhibitors (Matsuo et al, 2014; Ishikawa et al, 2018). There were several small molecule compounds from Chinese herbal medicine reported to be an inhibitor of TOPK to reduce the proliferation of tumor cells (Diao et al, 2019; Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%